The result of the aging process, whatever we choose to call it, is always negative (Agora for Physical Education and Sport, 2018)
In order to know how the processes of aging in our society are lived, a qualitative research was carried out based, mainly, on open interviews to elderly people of different ages. We present, on this occasion, some of the scientific evidences of the study: It is not easy to approach the collective because it is not even possible to find an appropriate name, accepted by everybody; whatever this process / stage is called, it always turns out to be something negative, and that’s the view of the participants in the study; nobody wants to belong or feel part of this collective, that is, in their explanations, the elders are (almost) always the others; and hegemonic body culture (e.g., the youth ideal) in our socio-cultural context directly influences the way of experiencing the process of becoming elderly, hence the need to understand it to reflect on the role that education professionals play in this regard.
Keywords: Aging; open interviews; aging denial; body culture